The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.22141/1608-1706.2.18.2017.102558
|View full text |Cite
|
Sign up to set email alerts
|

Експериментальне Моделювання Вибухових Переломів Грудопоперекового Відділу Хребта

Abstract: Актуальність. Вибухові переломи тіл нижньогрудного та поперекового відділів хребта є найбільш розповсюдженими серед усіх пошкоджень та становлять, за даними різних авторів, від 20 до 40 % усіх пошкоджень хребта. Мета: вивчити біомеханічні характеристики кіфотичної деформації в залежності від прикладеного осьового стискаючого навантаження, що діє вздовж усього хребта, та ступеня пошкодження хребтових структур. Матеріали та методи. Біомеханічна фізична модель вибухового перелому тіла Th12 хребця, що була виконан… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The results of this study revealed that there are no differences in disability or pain outcomes between operative and non-operative treatment of AOSpine A3 & A4 thoracolumbar burst fractures in neurologically intact patients, however authors of this study reported that it was not possible to evaluate the radiological outcomes due to the lack of uniform between analyzed articles [5]. Radchenko et al [6] conservative treatment. This study demonstrated that conservative and surgical (posterior short segment fixation PSSF-1 level above and 1 below) treatment modalities can provide satisfactory clinical results, however radiological outcomes showed advantages of the PSSF [6].…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…The results of this study revealed that there are no differences in disability or pain outcomes between operative and non-operative treatment of AOSpine A3 & A4 thoracolumbar burst fractures in neurologically intact patients, however authors of this study reported that it was not possible to evaluate the radiological outcomes due to the lack of uniform between analyzed articles [5]. Radchenko et al [6] conservative treatment. This study demonstrated that conservative and surgical (posterior short segment fixation PSSF-1 level above and 1 below) treatment modalities can provide satisfactory clinical results, however radiological outcomes showed advantages of the PSSF [6].…”
Section: Introductionmentioning
confidence: 71%
“…There is still conflicting evidence regarding non-surgical versus surgical treatment outcomes of thoracolumbar burst fractures without neurological deficit. In 2017, Rometsch et al [6] conducted the systematic literature review and meta-analysis, which was compared operative versus non-operative treatment for the AOSpine type A3 & A4 thoracolumbar burst fractures (T10-L3) in patients without neurological deficit. The results of this study revealed that there are no differences in disability or pain outcomes between operative and non-operative treatment of AOSpine A3 & A4 thoracolumbar burst fractures in neurologically intact patients, however authors of this study reported that it was not possible to evaluate the radiological outcomes due to the lack of uniform between analyzed articles [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation